Struktur Naratif Cerpen â€œAl-Imraâ€™at Ghalabati As-Syaitonâ€ Karya Taufiq El-Hakim (Kajian Naratologi A.J.Greimas) - Fatimah, Nisa; Supriadi, Dedi; Komarudin, Edi (Bahasa dan Sastra Arab, Fakultas Adab dan Humaniora, UIN Sunan Gunung Djati, 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â The aim in this study is 1) to learn scheme aktan contained in the short stories of women that trick the Devils work Taufiq el-Hakim, and 2) to find out the relationship between structure and functional structure aktan in the formation of structure the story. As for the method used in this research is descriptive method with the data gathering techniques in the form of the technique note and the study of librarianship. The source of the data in this study is the short story of the woman who deceived the Devils, and the data in this study is the word or phrase contained in the short stories of women that trick the Devils. Based on research conducted there is one schema aktan and functional model structure that exists in the text or sentence short women the Devils work beguiling Taufiq el-Hakim. The relationship between structure and functional structure aktan, there is one pattern that becomes aktan scheme structures the story namely aktan scheme contained in the short stories of women that trick the Devils work Taufiq el-Hakim. This gives rise to the existence of a aktansial scheme of events that become the structure of the story of the woman who deceived the Devils.Â Keywords: short stories of women that trick the Devils, aktan scheme, a functional structure, naratologi A.J. Greimas.Â Ù…Ù„Ø®Øµ Ø§Ù„Ø¨ØØ«Â ÙˆØ§Ù„Ø£ØºØ±Ø§Ø¶ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ 1) Ù„Ù…Ø¹Ø±ÙØ© Ù…Ø®Ø·Ø· Ø§Ù„Ø£ÙƒØªØ§Ù† ÙÙŠ Ù‚ØµØ© Ø§Ù„Ù‚ØµÙŠØ±Ø© Ø¥Ù…Ø±Ø£Ø© ØºÙ„Ø¨Øª Ø§Ù„Ø´ÙŠØ·Ø§Ù† Ù„ØªÙˆÙÙŠÙ‚ Ø§Ù„ØÙƒÙŠÙ….Â 2) Ù„Ù…Ø¹Ø±ÙØ© Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø¨ÙŠÙ† Ø¨Ù†ÙŠØ© Ø£ÙƒØªØ§Ù† Ùˆ Ù‡ÙŠÙƒÙ„ ÙˆØ¸ÙŠÙØªÙ‡ ÙÙŠ ØªØ´ÙƒÙŠÙ„ Ø¨Ù†ÙŠØ© Ø§Ù„Ù‚ØµØ©. Ø§Ø³ØªØ®Ø¯Ù… Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù…Ù†Ù‡Ø¬Ø§ ÙˆØµÙÙŠØ§ Ùˆ ÙˆÙŠØ³ØªØ®Ø¯Ù… Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù…Ù„Ø§ØØ¸Ø© ÙˆØ§Ù„ØªØ³Ø¬ÙŠÙ„ simak catat Ùˆ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù…ÙƒØªØ¨ÙŠØ© ÙˆØ£Ù…Ø§ Ù…ØµØ¯Ø± Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙÙŠ Ù‡Ø° Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ù‚ØµØ© Ù‚ØµÙŠØ±Ø©